1996
DOI: 10.1515/zna-1996-5-649
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of the Bismuth Oxide α — Bi2O3

Abstract: A very unusual magnetic behaviour of α - Bi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The SQUID-measurements of a-Bi 2 O 3 confirmed that it is not diamagnetic in the conventional sense [7,8]. The magnetization of a single crystal was positive at 4.2 K and highly anisotropic in magnetic fields H e up to 3j5 kOe [7].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The SQUID-measurements of a-Bi 2 O 3 confirmed that it is not diamagnetic in the conventional sense [7,8]. The magnetization of a single crystal was positive at 4.2 K and highly anisotropic in magnetic fields H e up to 3j5 kOe [7].…”
Section: Introductionmentioning
confidence: 69%
“…Although the explanation implying H loc is consistent with the observed spectra, no unambiguous proof of either the origin of the magnetism or the mechanism of ordering the magnetic moments over a wide temperature range (in a-Bi 2 O 3 , it exceeds 400-) is available at the moment. The bismuth 6sp-valence electrons (most probably, an unshared electron pair) bearing the effective magnetic moment m eff $ 0.1m B [7,8] are capable of producing the hyperfine filed (õ50 G) of the same order as that estimated from the NQR spectra, which suggests the hyperfine nature of H loc . It is reasonable to think that the ordering of so small a m eff over such a wide temperature range results from the ordering of the electric dipole moments via strong coupling between the magnetic and electronic systems of the compounds.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, according to the zerofield 2~ NQR data [1], supported by the resttlts of the SQUID measurements [10,11], a local magnetic field exists in ~t-Bi~O 3. As was mentioned above, the zero-fietd 2~ NQR spectrum of c~-Bi~O 3 appeared as typical Zeeman pattern: it displayed a quadruplet for vi and doublets for the lines of higher tran- SEE recorded for the v l transition in a powder Bi4Ge3012 sample is shown together with the split zero-field v l resonance given in the inset.…”
Section: Resultsmentioning
confidence: 96%
“…The existence of paramagnetic centers (holes in the unfilled p-electron shell of oxygen ions) was proposed as the origin of observed magnetoelectric effect in the α-Bi 2 O 3 single crystal [10]. The holes possess the magnetic moment due to spin and orbital magnetic moments.…”
Section: Discussionmentioning
confidence: 99%